Impacts of Soil Degradation: Case Study in Bogawantalawa South Grama Niladhari Division, Nuwara Eliya District, Sri Lanka - Krishnasoban, M.; Ruzaik, Fareena (International Journal of Research and Analytical Reviews, 2020)
Soil degradation is one of the crucial environmental problems in the Nuwara Eliya District in Sri Lanka. The main objective of this study is, analyzing impacts of the soil degradation in Bogawantalawa South Grama Niladhari Division (GND) of Nuwara Eliya District. The study applies purposive sampling method to select 186 samples from affected families for a questionnaire survey and field observations. Data has been analyzed, using the MS-Excel and SPSS software packages. This study found multifarious environmental impacts, such as loss soil of productivity, decreasing soil quality, water pollution, natural disasters and decreasing soil organism, sue to illegal gem mining and unplanned agricultural activities. This study recommends to minimize the soil degradation, by way of controlling illegal gem mining, using efficient irrigation methods, practicing sustainable soil conservation and farming, and strictly implementing existing soil conservation laws.
Keywords: Gem mining; Soil Degradation; Bogawantalawa